2020
DOI: 10.1371/journal.pone.0231859
|View full text |Cite
|
Sign up to set email alerts
|

Contextual and individual level factors influencing nutritional program effectiveness in HIV care setting in Tigray region, northern Ethiopia: Mixed methods study

Abstract: IntroductionAddressing malnutrition is one of the key components of HIV care among people living with HIV. Since 2010, a nutritional program has been implemented to address malnutrition amongst HIV patients in Ethiopia, with patients enrolled in the program for 3 months (for mild acute malnutrition) and 6 months (for severe acute malnutrition). However, utilisation and effectiveness of the nutritional programs remain unexplored. This study aimed to examine individual level determinants and contextual factors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(41 citation statements)
references
References 47 publications
4
37
0
Order By: Relevance
“…A rural residence is described as a barrier to nutritional recovery. This was in concordance with other studies performed in different parts of Africa [ 17 , 21 ]. The mechanism by which rural residence leads to poor nutritional recovery in HIV patients remains unclear, but it might be because rural settings would have high levels of poverty and difficulties in accessing different health services.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A rural residence is described as a barrier to nutritional recovery. This was in concordance with other studies performed in different parts of Africa [ 17 , 21 ]. The mechanism by which rural residence leads to poor nutritional recovery in HIV patients remains unclear, but it might be because rural settings would have high levels of poverty and difficulties in accessing different health services.…”
Section: Discussionsupporting
confidence: 94%
“…This study revealed that from the total patients who were on the therapeutic feeding program, nearly two-thirds of patients were recovered from undernutrition, which is comparable with a study done in Mekelle Hospital, Ethiopia [ 16 ], but it is higher when compared with studies conducted in different parts of sub-Saharan Africa including Ethiopia [ 17 20 ]. Most importantly, the current findings support WHO recommendations that nutritional counseling and therapy should be implemented for undernourished HIV patients.…”
Section: Discussionsupporting
confidence: 80%
“…A key issue also identi ed as a challenge for nutrition counselling programs was a lack of focus on the context of people's lives. This study found that food insecurity and poverty were a key issue among people living with HIV enrolled in the nutritional program [38] that affected their capacity to implement some elements of the counselling. Other studies in Kenya [50], South Africa, and Ghana [51,58] have likewise demonstrated the importance of considering the individual patient's nancial and socioeconomic circumstances when providing the nutritional counselling for better effectiveness.…”
Section: Discussionmentioning
confidence: 92%
“…This study is part of a larger study that examined the determinants of nutritional outcomes and challenges of a nutritional program in the Tigray region of Ethiopia [37,38]. This paper presents ndings from a qualitative study involving individual interviews with adults living with HIV, caregivers of children living with HIV, health providers, and health managers to explore their experiences and perspectives about nutritional counselling in the nutritional program in HIV care settings.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation